KOMPARASI BUDAYA JEPANG DAN PRANCIS MELALUI KOMIK DETEKTIF - Tania Intan (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2018)
Psychologically, humans have a tendency to love reality and fiction because of life in between. With its unlimited imagination, humans can choose the preferred model of reality or fiction. If he chooses to be a good observer, a good and patient guesser in waiting for answers to important questions, the detective story can be an interesting reading alternative. In general, the detective story developed along with the rapid urbanization as a result of the industrial revolution. Life in big cities becomes insecure because of the increasing population density, unemployment, poverty and crime. To be able to reduce the saturation and tension experienced everyday, the public also entertain themselves with reading. Apparently people love reading about mysterious or even frightening events, because it always ends with a rational explanation of the various puzzles that cling to the reading. The crime-themed book makes readers familiar with the presence of criminals and law enforcers who are hunting him. Comics also called 'image literature', can also be a medium of telling of crimes favored by various circles. In this paper, we will discuss the phenomenon of the existence of detective comics in France and Japan with cultural comparative methods and studied with relevant theories. The results showed that because they came from different cultural backgrounds and published times, several things were found that showed differences between French and Japanese detective comics, including those related to characterization, public, story and cultural backgrounds, and comic formats. While the things that are common among them are the profession of detective figures who work more independently and prominently, and the presence of local police who are supportive of the character's movements, despite the fact that they often arrive late at the scene.